Tempo e arte: note per una fenomenologia - De Gennaro, Ivo (Bollettino Filosofico, 2018)
Phenomenological thinking looks upon art not merely as a possible object of philosophical investigation, carried out by a specific discipline, i.e. aesthetics; rather, it considers art – notably its provenance and destination – as a hermeneutic task capable of furthering the scope of thinking itself. In other words: phenomenology understands itself as paving the way for a new style of thinking precisely thanks to, and through, its dialogue with art, aimed at letting art speak as and for itself. The status of art as a constitutive task for thinking shows in a particularly marked manner when basic notions such as truth, space and time explicitly become the “subject matter” of art in ways that traditional philosophical understanding of those notions does not seem to be able to adequately grasp. This essay tentatively examines a few instances of 20th century artistic approaches to time – notably in music, painting and sculpture – in order to outline the hermeneutic task that they pose to contemporary thinking. The interpretive horizon for this outline is provided by Heidegger’s later reflection on time, as can be found i.a. in his posthumous treatise Beiträge zur Philosophie (Vom Ereignis).